KONSEP PEMBELAJARAN PESANTREN SEBAGAI MODEL HOLISTIK BERBASIS AGAMA DI SMP ISLAM BUSTANUL ISLAM LAMONGAN - Febi Hidayatul Ilmiya; Ilma Maulidah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the concept of pesantren-based learning as a model of holistic religious education at SMP Islam Bustanul Hikmah Lamongan. Using a qualitative case study approach, the research involved the principal, teachers, and students, with data collected through interviews, participatory observation, and documentation. The findings show that the pesantren applies a Full Day School model integrating religious and general curricula. Learning methods such as Sorogan, Musyawaroh, and Tiqror are combined with special programs like Yanbu’a, Tahfidz, and Kitab Kuning. Daily practices, including salat dhuha and salat hajat, help strengthen students’ character and discipline. Challenges related to administrative requirements and teacher professionalism are addressed through curriculum training, specialized method training, and professional staff support. This integrative approach fosters balanced and adaptive holistic education.